2018
DOI: 10.3390/nu10070810
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of C. butyricum Sx-01 and L. salivarius C-1-3 Improves Intestinal Health and Reduces the Amount of Lipids in Serum via Modulation of Gut Microbiota in Mice

Abstract: The study was conducted to investigate whether combined use of C. butyricum Sx-01 and L. salivarius C-1-3 could improve the intestinal health and reduce the lipid levels in sera of mice and whether these benefits were related to regulating the intestinal microflora. Eighty Kunming male mice were divided into four groups with five replicates per group and four mice per replicate. Mice in the control group were administrated with 0.2 mL normal saline; mice in three experimental groups were daily orally administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…For example, the length of the intestinal villi is improved by feeding pigs LAB (1820) and broilers BAB (21). Moreover, Long et al (22) reported that the combined use of LAB and BAB could further improve the length of the intestinal villi in mice. Therefore, since we were unable to investigate factors associated with intestinal health in the present study, we cannot rule out the possibility that the combined use of LAB and BAB has synergistic effects on factors other than growth parameters and the microbiota of post-weaning pigs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the length of the intestinal villi is improved by feeding pigs LAB (1820) and broilers BAB (21). Moreover, Long et al (22) reported that the combined use of LAB and BAB could further improve the length of the intestinal villi in mice. Therefore, since we were unable to investigate factors associated with intestinal health in the present study, we cannot rule out the possibility that the combined use of LAB and BAB has synergistic effects on factors other than growth parameters and the microbiota of post-weaning pigs.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Introducing C. butyricum has been shown to protect properties of the mucosal layer in two different mouse models. Administration of C. butyricum Sx-01 significantly increased colonic mucosal thickness in a murine study of probiotic supplementation for general intestinal health, 25 while administration of CBM 588 increased mucin production (measured as increased expression of MUC2) and significantly decreased epithelial damage in the colonic tissue of mice with clindamycin-induced antibioticassociated diarrhea. 15 The effect of C. butyricum on mucosal health may be explained by its capacity for butyrate production.…”
Section: Butyricum Strengthens the Gut Barriermentioning
confidence: 95%
“…Also, the bacteria in the intestines, including large intestines, reflects the body's immune activity to a certain extent [42]. The increase in the length of the large intestinal villi can enhance the digestion and absorption of food and the height of the large intestine villi and the depth of the intestinal crypt are known indicators of intestinal function and intestinal health [31]. Goblet cells of the intestinal mucosal epithelium secrete mucin, forming an intestinal mucosal epithelial barrier to separate intestinal bacteria and epithelial cells [43].…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin & eosin (H-E; Sigma-Aldrich, St. Loise, MO, USA) staining was conducted to measure epidermis and dermis thickness, abnormality of cells and nucleus in the keratocytes and the surface of the skin. The intestinal histology of the large intestines (villous length, intestinal crypt, the width of intestinal villi) was evaluated in H-E staining [31]. Toluidine blue (Sigma-Aldrich, St. Loise, MO, USA) staining was also performed to calculate the number of mast cells in the tissues (%).…”
Section: Histopathological Analysismentioning
confidence: 99%